Faktor-Faktor yang Berhubungan dengan Pemberian Kolostrum Pada Hari Pertama Kelahiran - Ari Sita Dewi; Ni Made Nurtini; Ni Komang Sri Ariani (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2025)
Nutrition provided through breast milk (ASI) has substantial implications for the quality of a child's development. Observations conducted in the Postpartum Ward of Klungkung Regional Hospital indicate that some breastfeeding mothers do not provide colostrum to their babies, this occurs quite frequently. Factors underlying the lack of colostrum include knowledge, education, and family support. This study is an analytical survey study with a cross-sectional design. Respondents were 80 postpartum mothers selected using a purposive sampling technique at Klungkung Regency Hospital during the period March-April 2025. The research instrument used a questionnaire. Univariate analysis focused on frequency distribution, while bivariate analysis used the Spearman Rank test. The results showed that the majority of respondents showed a sufficient level of knowledge (66 mothers (82.5%), a high school education background (66 mothers (82.5%), and family support was considered sufficient (50 mothers (62.5%). Statistical analysis using the Spearman Rank Test obtained a value of 0.001 (p <0.05). These results indicate a significant correlation between maternal knowledge, education, and family support levels and the practice of providing colostrum on the first day of birth in the postpartum ward at Klungkung District Hospital. Healthcare workers are expected to routinely provide education and counseling to breastfeeding mothers to improve colostrum provision on the first day of birth.